2018
DOI: 10.1016/j.otsr.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy-assisted Trillat procedure for anterior shoulder instability: Surgical technique and preliminary clinical results

Abstract: The Trillat procedure performed as open surgery to treat anterior shoulder instability has been proven effective in preventing recurrences and restoring range of motion. An arthroscopically assisted variant of the Trillat procedure is described here, together with the preliminary clinical results in 18 patients treated between 2011 and 2014. After a mean follow-up of 24.7±9.8 months, the clinical outcomes were very satisfactory, with a Walch-Duplay score of 81.5±18.0, a Rowe score of 83.6±16.0, and 94% of sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Walch et al 2 reported 96% patient satisfaction with more than 10 years of follow up in patients with anterior instability with massive irreparable cuff tears. Ongoing instability has been reported as 16% by Walch et al 2 , by Gerber et al 5 as 4% recurrent dislocation but 18% recurrent apprehension, and recently by Labattut et al 8 as 5.5% in a short-term follow-up of arthroscopically assisted open Trillat procedures. In both articles by Walch et al 2 and Gerber et al, 5 they reported glenohumeral osteoarthritis at final follow-up of 64.3% and 62%, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Walch et al 2 reported 96% patient satisfaction with more than 10 years of follow up in patients with anterior instability with massive irreparable cuff tears. Ongoing instability has been reported as 16% by Walch et al 2 , by Gerber et al 5 as 4% recurrent dislocation but 18% recurrent apprehension, and recently by Labattut et al 8 as 5.5% in a short-term follow-up of arthroscopically assisted open Trillat procedures. In both articles by Walch et al 2 and Gerber et al, 5 they reported glenohumeral osteoarthritis at final follow-up of 64.3% and 62%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Our arthroscopic Trillat technique is simpler and less technically demanding than arthroscopic Latarjet procedures, making it a good initial procedure for surgeons wanting to transition to extra-articular arthroscopic stabilization procedures (Table 3). An important advantage of this technique, compared with other open or arthroscopic Trillat techniques, 8,9 is the lack of release of the pectoralis minor tendon from the coracoid process. This negates the need for dissection medial to the coracoid process and thus reduces the risk of serious intraoperative bleeding and damage to the musculocutaneous and axillary nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Labattut et al 10 . reported a 5.5% recurrence rate and satisfactory functional results at short-term follow-up after arthroscopically assisted Trillat procedure for chronic anterior instability.…”
Section: Discussionmentioning
confidence: 99%
“…Labattut et al. 20 described an arthroscopy-assisted Trillat procedure for anterior shoulder instability in 18 patients as a simple and reproductive alternative to arthroscopic Latarjet procedure. They found at a median follow-up of 24.7 months very satisfactory clinical outcomes with 94% of satisfied or very satisfied patients and no recurrences recorded.…”
Section: Discussionmentioning
confidence: 99%
“…It allows the assessment of the subscapularis at the end of the procedure to prevent any infra-coracoid impingement (which may lead to a loss of external rotation) as the treatment of associated lesions. 19 Labattut et al 20 described an arthroscopy-assisted Trillat procedure for anterior shoulder instability in 18 patients as a simple and reproductive alternative to arthroscopic Latarjet procedure. They found at a median follow-up of 24.7 months very satisfactory clinical outcomes with 94% of satisfied or very satisfied patients and no recurrences recorded.…”
Section: Discussionmentioning
confidence: 99%